ANALISIS PERBEDAAN PERSEPSI TENTANG MUTU PELAYANAN ANTARA PASIEN RUJUKAN PETUGAS DENGAN PASIEN KEMAUAN SENDIRI DI PELAYANAN RAWAT INAP GERIATRI RUMAH SAKIT dr. KARIADI SEMARANG - Widayati, Sri; Kurniawan, Arif (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2008)
Based to visit data year 2005 known that from amount of 238 patient there are amount of referred patient from health officer more that is 171 patient (71,85%) compared to patient who taken care with their willingness counted 67 patient (28,15%). Therefore, it requires to know patient's preception especially about the take care service of to lodge in Division of Geriatri both of reffered and chosening their room with theirselves as base of posisioning or marketing promotion next. The purpose of this research is to know the difference perception about the take care service of to lodge in Division of Geriattri both of referred and chosening theur room with theirselves as base of posisioning or marketing promotion next. The purpose of this reseaech is to know the difference perception about the  take care service of to lodge to old age between reference patient from health officer and patient who taken care with their willingness in division of Geriatri Hospital of dr Kariadi Semarang. This research used observation with method of survey, to explain the relation between variable independent and variabke dependent. This research not only quantitative approach, but also with qualitative approach by using indepth interview to get input about take care service of to lodge and promotion which have been done.the time approach of data collecting use study of crosssectional.this research not only quantitative approach, but also with qualitative approach by using indepth interview to get input about takecare service of to lodge and promotion which have been done. The time approach of data collecting use study of crossectional. This research population is all patient who take care of to lodge in two month range of time in take care room of to lodge division of Geriatri Hosputal of dr Kariyadi Semarang. This research sample amount to 62 people, consist of31 reference patient from health officer group ND 31 Patient with their willingness group. Analyse bivariate in this research is analysis of mann whitney. Analysis Multivariant usesanalysis of Mannova. Resukt of biavariate analysis shiws, there is not diferennce perception between patient take care of lodge who is reffered by healt officer and patien who choicening with their selves about reability service (p=0,207), perception about responsiveness service (p=0,598) , perception about assurance service (p=0,425), perception about tangible service (p=0,121), and perception about emphaty service (p=0,797). Result of analysis of multivariate indicate that there was not different together perception about reability service (p-0,292), perception about responsiveness service (p=0,292)and perception aboutassurance service (p=0,292), perception about tangible service (P=0,393) and perception about empathy service (p=0,292) between reference patient from health officer and willingness patient?s self. The conclusion of this researchis reference patient from health officer and willingness patiens self had the same perception about service quality. There is not difference together perception perception about reliability service, responsiveness service, assurance service, tangible service and empathy service from health officer and willingness patient self. Suggestion for the management of Geriatri division dr Kariadi Senarang have to upgrades service and improve service promotion to old age society.